Solid composition, method for producing solid composition, powder coating material and method for producing coated article
By using a solid composition of a fluorinated copolymer of trifluorochloroethylene and vinyl ether units, piperidinyl compounds, and mixed xylenes, the problem of insufficient lightfastness and impact resistance of powder coatings was solved, resulting in superior coating performance.
Patent Information
- Application Number
- CN202480017526.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-10
- Filing Date
- 2024-02-20
- Publication Date
- 2025-10-31
AI Technical Summary
There is still room for improvement in the light resistance and impact resistance of existing powder coatings.
A solid composition comprising a fluorinated copolymer having trifluorochloroethylene and vinyl ether units, a compound containing piperidine groups, ethylbenzene, and mixed xylenes is polymerized and solvent removed to form a powder coating, thereby improving the lightfastness and impact resistance of the coating film.
This results in a coating film with excellent lightfastness and impact resistance, improving the film's durability and performance.
Smart Images

Figure BDA0005585099210000091 
Figure BDA0005585099210000121 
Figure BDA0005585099210000271
Abstract
Description
Technical Field
[0001] This invention relates to solid compositions, methods for manufacturing solid compositions, powder coatings, and methods for manufacturing coated articles. Background Technology
[0002] Coatings containing fluorinated copolymers can form films with excellent durability, and therefore, they are attracting attention from both economic and environmental perspectives as materials that can reduce the life cycle cost of coated items. Among these coatings containing fluorinated copolymers, powder coatings are widely used as they are among the least environmentally burdensome.
[0003] Patent Document 1 discloses a method for manufacturing powder coatings using a solution containing a fluororesin as a raw material, wherein the solution containing the fluororesin comprises a fluorinated copolymer having trifluorochloroethylene-based units, an amino-containing compound (a compound containing a piperidine group), and xylene.
[0004] Existing technical documents
[0005] Patent documents
[0006] Patent Document 1: International Publication No. 2017 / 122701 Summary of the Invention
[0007] The problem the invention aims to solve
[0008] In recent years, there has been an increasing demand for improved performance of coatings obtained using powder coatings, specifically, the need to further enhance lightfastness and impact resistance.
[0009] When the inventors manufactured a solid composition comprising a fluorinated copolymer, a piperidine-containing compound, and xylene by referring to the composition of a fluorinated resin solution described in Patent Document 1, and formed a powder coating film using the composition, they found that there was room for improvement, at least in terms of the impact resistance of the coating film.
[0010] The present invention was made in view of the above-mentioned problems, and its objective is to provide a solid composition capable of forming a coating film with excellent lightfastness and impact resistance, a method for manufacturing the solid composition, a method for manufacturing powder coatings and coated articles.
[0011] Solution for solving the problem
[0012] The inventors conducted in-depth research on the above-mentioned issues and found that when a solid composition comprising a fluorinated copolymer having trifluorochloroethylene-based units and vinyl ether-based units, a compound containing piperidinyl groups, ethylbenzene, and a mixture of xylenes containing o-xylene, m-xylene, and p-xylene is used as a raw material for powder coatings, the coating film formed by using the powder coating exhibits excellent lightfastness and impact resistance, thus completing the present invention.
[0013] That is, the inventors have discovered that the above-mentioned problems can be solved by the following technical solution.
[0014] [1] A solid composition characterized in that it comprises: a fluorinated copolymer having trifluorochloroethylene-based units and vinyl ether-based units; a compound containing piperidinyl groups; ethylbenzene; and a mixture of xylenes containing at least two of o-xylene, m-xylene and p-xylene.
[0015] [2] The solid composition according to [1], wherein the above-mentioned mixed xylene contains all of o-xylene, m-xylene and p-xylene.
[0016] [3] The solid composition according to [1] or [2], wherein the mass ratio of the content of the ethylbenzene to the content of the mixed xylene is 0.1 to 7.0.
[0017] [4] The solid composition according to any one of [1] to [3], wherein the above-mentioned compound containing piperidine group is a compound represented by the formula (N1) described later.
[0018] In the following formula (1),
[0019] R 11 ~R 14 Each is independently an alkyl, cycloalkyl, substituted alkyl, aryl, or aralkyl group having 1 to 18 carbon atoms, R 11 and R 12 Or R 13 and R 14 It can be optionally formed into an aliphatic ring with 3 to 6 carbon atoms;
[0020] R 15 It can be a hydrogen atom, alkyl, substituted alkyl, aryl, aralkyl, or cycloalkyl;
[0021] R 16 It is a group consisting of a hydrogen atom, a hydroxyl group, an alkyl group, a substituted alkyl group, an aryl group, an aralkyl group, a group containing an ester bond, a group containing an amino group, a group containing a 2,2,6,6-tetrasubstituted piperidinyl group, or a combination of two or more of these groups.
[0022] [5] The solid composition according to any one of [1] to [4], wherein the content of the above-mentioned piperidinyl compound is 0.01 to 3.0% by mass relative to the total mass of the above-mentioned solid composition.
[0023] [6] The solid composition according to any one of [1] to [5], wherein the mass ratio of the content of the above-mentioned piperidinyl compound to the content of the above-mentioned ethylbenzene is 0.5 to 200.
[0024] [7] A method for manufacturing a solid composition, characterized in that a monomer comprising trifluorochloroethylene and vinyl ether is polymerized in the presence of a polymerization solvent, a piperidine-containing compound and a free radical polymerization initiator to produce a solution comprising a fluorinated copolymer, the polymerization solvent and the piperidine-containing compound, wherein the polymerization solvent comprises ethylbenzene and a mixture of xylenes containing o-xylene, m-xylene and p-xylene, and at least a portion of the polymerization solvent is removed from the solution to obtain a solid composition comprising the fluorinated copolymer, the piperidine-containing compound, the ethylbenzene and the mixture of xylenes.
[0025] [8] A powder coating, characterized in that it comprises the fluorinated copolymer, the piperidine compound, ethylbenzene, and the mixed xylene containing o-xylene, m-xylene and p-xylene contained in any of the solid compositions described in any one of [1] to [6].
[0026] [9] A method for manufacturing a coated article, characterized in that the powder coating described in [8] is applied to the surface of a substrate to form a coating layer, and the coating layer is cured to form a coating film.
[0027] The effects of the invention
[0028] According to the present invention, solid compositions capable of forming coatings with excellent lightfastness and impact resistance, methods for manufacturing solid compositions, powder coatings, and methods for manufacturing coated articles can be provided. Detailed Implementation
[0029] The meanings of the terms used in this invention are as follows.
[0030] The numerical range indicated by "~" refers to the range of values included before and after the "~" as lower and upper limits. Within the numerical ranges described in this specification, the upper or lower limit value described within a certain numerical range can be replaced by the upper or lower limit value of other numerical ranges described in different stages. Furthermore, within the numerical ranges described in this specification, the upper or lower limit value described within a certain numerical range can be replaced by the values shown in the embodiments.
[0031] In this specification, each component may be used alone with one substance that conforms to that component, or in combination with two or more substances. Here, when two or more substances are used in combination for each component, the relevant content of that component refers to the total content of the combined substances unless otherwise specified.
[0032] In this specification, a combination of two or more preferred methods is a more preferred method.
[0033] A unit refers to a group of atoms formed directly from the polymerization of monomers, based on one molecule of the aforementioned monomer, as well as groups of atoms obtained by chemically transforming a portion of the aforementioned groups. The content (mol%) of each unit relative to all units contained in the polymer can be determined by analyzing the polymer using nuclear magnetic resonance spectroscopy, or it can be determined based on the amount of components used in the manufacture of the polymer.
[0034] (Meth)acryloyl refers to the collective name for acryloyl and methacryloyl groups.
[0035] Hydrolyzable silyl groups are groups that can form silanol groups through hydrolysis.
[0036] The acid value and hydroxyl value were measured according to the method of JIS K 0070-3 (1992).
[0037] The glass transition temperature (Tg) is the intermediate glass transition temperature of a polymer, determined by differential scanning calorimetry (DSC).
[0038] Melt viscosity is the value of the sample at 170°C when heated from 130°C to 200°C using a rotary rheometer at a heating rate of 10°C / min.
[0039] Number-average molecular weight (Mn) and weight-average molecular weight (Mw) are values measured using size exclusion chromatography (gel permeation chromatography) with polystyrene as a standard. Additionally, the ratio of Mw to Mn represents the molecular weight distribution, also known as Mw / Mn.
[0040] The average particle size refers to the 50% diameter value calculated from the volume average of the particle size distribution measured using a known particle size distribution measuring device (Sympatec, trade name: Helos-Rodos, etc.) based on the principle of laser diffraction.
[0041] The film thickness is a value measured using an eddy current film thickness gauge (SANKO ELECTRONIC, trade name: EDY-5000, etc.).
[0042] The solid composition of the present invention (hereinafter also referred to as the solid composition) comprises: a fluorinated copolymer having trifluorochloroethylene-based units and vinyl ether-based units (hereinafter also referred to as a specific fluorinated copolymer); a compound containing piperidinium; ethylbenzene; and a mixture of xylenes containing o-xylene, m-xylene and p-xylene.
[0043] When this solid composition is used as a raw material for powder coatings, the resulting coating exhibits excellent lightfastness and impact resistance. The reason for this may not be clear, but it can be considered as follows.
[0044] A coating film obtained using powder coatings is, for example, obtained by applying the powder coating to the surface of a substrate to form a coating layer, and then subjecting the coating layer to heat treatment. When the coating layer is heated, components of the powder coating that vaporize upon heating (e.g., solvents such as ethylbenzene and mixed xylenes) are gradually removed from the coating layer. It can be understood that air present between the powder particles constituting the coating layer is gradually removed from the coating layer through pathways formed by the vaporized components.
[0045] Therefore, it can be concluded that when multiple compounds with different boiling points exist as vaporization components, compared to the case where there is only one vaporization component, air passages corresponding to the boiling points of the vaporization components are formed in stages, thus increasing the air removal time. As a result, it can be inferred that a coating with fewer pores (voids) is formed, thereby improving the coating's impact resistance.
[0046] Furthermore, it can be assumed that by including ethylbenzene in this solid composition, the piperidine-containing compound, which contributes to improved lightfastness, is uniformly dispersed in the coating film. Therefore, it can be inferred that the lightfastness of the coating film is improved.
[0047] In this invention, a solid composition refers to a solid component with a mass percentage of 97.0% or more.
[0048] Here, the mass of the solid components can be calculated based on the mass before and after drying, and the specific determination method is shown below.
[0049] First, weigh 0.25 g of the solid composition and add it to a metered aluminum cup. Add 4 g of toluene and allow the solid composition to dissolve completely. Then, heat the mixture at 110°C for 3 hours using a hot air circulating dryer. Next, measure the aluminum cup after the test and determine the mass of the residue. Calculate the mass of the solid component using the following formula.
[0050] Mass of solid components (mass%) = 100 × (mass of residue) / (mass of solid composition)
[0051] Certain fluorinated copolymers have units based on trifluorochloroethylene (CF2=CFCl) and units based on vinyl ethers.
[0052] From the viewpoint that the coating obtained by using a specific fluorinated copolymer has better weather resistance, the content of trichlorofluoroethylene-based units relative to all repeating units of the specific fluorinated copolymer is preferably 30 to 70 mol%, more preferably 40 to 60 mol%, and even more preferably 45 to 55 mol%.
[0053] Vinyl ethers can be vinyl ethers with crosslinking groups or vinyl ethers without crosslinking groups.
[0054] From the viewpoint that the durability of coatings obtained using specific fluorinated copolymers can be further improved, vinyl ethers preferably have crosslinking groups.
[0055] Specific examples of crosslinking groups include at least one group selected from the group consisting of hydroxyl, amino, epoxy, oxetyl, hydrolyzable silyl, sulfonyl, and carboxyl. From the viewpoint of further improving the hardness of the coating film obtained using the specific fluorinated copolymer, hydroxyl or carboxyl is preferred, and hydroxyl is more preferred. It should be noted that sulfonyl and carboxyl groups can be ionized to form -SO3. - or -COO - It can also form salts with cations to become -SO3. - Na + or -COO - Na + wait.
[0056] The number of cross-linking groups can be one or more. Two or more types of cross-linking groups can be used in combination.
[0057] Vinyl ethers can be used in combination of two or more types, with the preferred method being the combination of vinyl ethers having crosslinking groups and vinyl ethers not having crosslinking groups.
[0058] Vinyl ethers may or may not have fluorine atoms, but are preferably free of fluorine atoms.
[0059] Vinyl ethers with crosslinking groups can be used in combination of two or more types.
[0060] Specific examples of vinyl ethers containing hydroxyl groups include CH2=CHO-CH2-cycloC6H. 10 -CH2OH, CH2=CHOCH2CH2OH, CH2=CHOCH2CH2CH2CH2OH.
[0061] It should be noted that "-cycloC6H" 10 - indicates subcyclohexyl group, "-cycloC6H" represents the group with the cyclohexyl group. 10 The bonding site of "-" is usually 1,4-.
[0062] Vinyl ethers containing hydroxyl groups can be used in combination of two or more.
[0063] A specific example of a vinyl ether containing a carboxyl group is CH2=CHO(CH2). n12 The monomer shown in OC(O)CH2CH2COOH (where n12 represents an integer from 1 to 10).
[0064] Vinyl ethers with carboxyl groups can be used in combination of two or more.
[0065] Specific examples of vinyl ethers that do not have crosslinking groups include ethyl vinyl ether, tert-butyl vinyl ether, 2-ethylhexyl vinyl ether, cyclohexyl vinyl ether, and cyclohexylmethyl vinyl ether.
[0066] Vinyl ethers without crosslinking groups can be used in combination of two or more types.
[0067] The content of vinyl ether-based units relative to all repeating units of a particular fluorinated copolymer is preferably 1 to 80 mol%, more preferably 10 to 70 mol%, and even more preferably 20 to 60 mol%.
[0068] When the vinyl ether-based unit includes a unit based on a vinyl ether having a crosslinking group, from the viewpoint of further improving the durability of the coating obtained using the specific fluorinated copolymer, the content of the unit based on the vinyl ether having a crosslinking group is preferably 1 to 30 mol% relative to all repeating units of the specific fluorinated copolymer, more preferably 3 to 25 mol%, and even more preferably 5 to 20 mol%.
[0069] When the vinyl ether-based unit includes a unit based on a vinyl ether without crosslinking groups, from the viewpoint of further improving the smoothness and hardness of the coating obtained using the specific fluorinated copolymer, the content of the unit based on the vinyl ether without crosslinking groups is preferably 1 to 70 mol% relative to all repeating units of the specific fluorinated copolymer, more preferably 5 to 60 mol%, and even more preferably 10 to 50 mol%.
[0070] A particular fluorinated copolymer may contain units other than those based on trifluorochloroethylene and those based on vinyl ether (hereinafter also referred to as other units), but from the viewpoint that the coating obtained by using a particular fluorinated copolymer has superior lightfastness, it is preferable that it does not contain other units in substantial terms.
[0071] Here, "substantially free of other units" means that the content of other units is less than 0.1 mol% relative to all repeating units of a particular fluorinated copolymer.
[0072] Specific examples of other units include units based on fluoroolefins other than trifluorochloroethylene and units based on vinyl esters.
[0073] From the viewpoint of being able to further improve the hardness of the coating film obtained using a specific fluorinated copolymer, the specific fluorinated copolymer preferably does not have carboxyl groups. In this case, the specific fluorinated copolymer preferably has hydroxyl groups.
[0074] The specific fluorinated copolymer preferably comprises units based on trifluorochloroethylene, units based on vinyl ethers with crosslinking groups, and units based on vinyl ethers without crosslinking groups; more preferably, it is a fluorinated copolymer substantially composed of units based on trifluorochloroethylene, units based on vinyl ethers with crosslinking groups, and units based on vinyl ethers without crosslinking groups; and even more preferably, it is a fluorinated copolymer composed only of units based on trifluorochloroethylene, units based on vinyl ethers with crosslinking groups, and units based on vinyl ethers without crosslinking groups.
[0075] "A fluorinated copolymer substantially composed of units based on trifluorochloroethylene, units based on vinyl ethers with crosslinking groups, and units based on vinyl ethers without crosslinking groups" means that the content of other units besides the units based on trifluorochloroethylene, the units based on vinyl ethers with crosslinking groups, and the units based on vinyl ethers without crosslinking groups is less than 0.1 mol% relative to all repeating units of a particular fluorinated copolymer.
[0076] In a specific fluorinated copolymer, the contents of trifluorochloroethylene-based units, vinyl ether-based units with crosslinking groups, and vinyl ether-based units without crosslinking groups, relative to all units contained in the specific fluorinated copolymer, are preferably 30-70 mol%, 1-30 mol%, and 1-70 mol%, respectively; more preferably, the contents are 45-55 mol%, 5-20 mol%, and 10-50 mol%, respectively.
[0077] From the viewpoint of further improving the anti-blocking properties of powder coatings containing specific fluorinated copolymers and the surface smoothness of coatings obtained by using the above-mentioned powder coatings, the Tg of the specific fluorinated copolymer is preferably 20 to 60°C, more preferably 25 to 60°C, and even more preferably 30 to 55°C.
[0078] The melt viscosity of a specific fluorinated copolymer at 170°C is preferably 0.1–450 Pa·s, more preferably 1–450 Pa·s, and even more preferably 3–400 Pa·s.
[0079] When a specific fluorinated copolymer has a hydroxyl value, the hydroxyl value of the specific fluorinated copolymer is preferably greater than 0 mg KOH / g and less than 150 mg KOH / g, more preferably 5 to 120 mg KOH / g, even more preferably 15 to 110 mg KOH / g, and particularly preferably 30 to 100 mg KOH / g. When a specific fluorinated copolymer has an acid value, the acid value of the specific fluorinated copolymer is preferably greater than 0 mg KOH / g and less than 10 mg KOH / g, more preferably 2 to 8 mg KOH / g, and even more preferably 3 to 7 mg KOH / g.
[0080] From the viewpoint of achieving better results with the present invention, the Mw of the specific fluorinated copolymer is preferably 10,000 to 60,000, more preferably 12,000 to 55,000, and even more preferably 15,000 to 50,000.
[0081] From the viewpoint of achieving better results with the present invention, the Mn of the specific fluorinated copolymer is preferably 5,000 to 20,000, more preferably 6,000 to 18,000, and even more preferably 7,000 to 16,000.
[0082] From the viewpoint of achieving better results with the present invention, the Mw / Mn (molecular weight distribution) of the specific fluorinated copolymer is preferably 2.0 to 3.5, more preferably 2.1 to 3.3, and even more preferably 2.2 to 3.2.
[0083] The content of the specific fluorinated copolymer relative to the total mass of the solid composition is preferably 98.1 to 99.9% by mass, more preferably 98.5 to 99.9% by mass, and even more preferably 99.0 to 99.8% by mass. If the content of the specific fluorinated copolymer is 98.1% by mass or more, the anti-blocking properties are excellent. Furthermore, if the content of the specific fluorinated copolymer is 99.9% by mass or less, the impact resistance of the coating film is excellent.
[0084] Compounds containing piperidine groups can be derived from components used in the manufacture of a particular fluorinated copolymer or from substances added during the manufacture of this solid composition.
[0085] Compounds containing piperidinium are compounds containing piperidinium or piperidinium with substituents, more preferably compounds containing piperidinium with substituents.
[0086] The piperidinyl group having substituents is preferably tetrasubstituted piperidinyl, more preferably 2,2,6,6-tetrasubstituted piperidinyl.
[0087] The preferred compounds containing piperidinium are those containing two or more piperidinium groups or piperidinium groups with substituents.
[0088] It is preferred to use two or more compounds containing piperidine groups.
[0089] From the viewpoint of further improving the lightfastness of the coating film, compounds containing piperidine groups are preferably compounds represented by the following formula (N1) (compounds having 2,2,6,6-tetrasubstituted piperidine groups).
[0090]
[0091] R 11 ~R 14Each is independently an alkyl, cycloalkyl, substituted alkyl, aryl, or aralkyl group having 1 to 18 carbon atoms, R 11 and R 12 Or R 13 and R 14 It can form aliphatic rings with 3 to 6 carbon atoms. As R 11 ~R 14 From the viewpoint of price and ease of acquisition, alkyl groups with 1 to 18 carbon atoms are preferred, and methyl groups are particularly preferred.
[0092] Specific examples of alkyl groups having 1 to 18 carbon atoms include methyl, ethyl, propyl, dodecyl, stearyl, etc., with methyl being preferred as described above.
[0093] Specific examples of the aforementioned cycloalkyl groups include cyclopentyl and cyclohexyl.
[0094] The aforementioned substituted alkyl group is an alkyl group having a substituent at any position. Examples of such substituents include hydroxyl and alkoxy groups. Specific examples of the aforementioned substituted alkyl group include 2-hydroxyethyl, 2-methoxycarbonylethyl, and 3-hydroxypropyl.
[0095] Specific examples of the aforementioned aryl groups include phenyl and naphthyl groups.
[0096] Specific examples of the aforementioned aralkyl groups include phenethyl and benzyl.
[0097] R 15 It can be a hydrogen atom, alkyl, substituted alkyl, aryl, aralkyl or cycloalkyl.
[0098] Specific examples of the aforementioned alkyl groups include methyl, ethyl, propyl, butyl, dodecyl, and stearyl.
[0099] The aforementioned substituted alkyl group is an alkyl group having a substituent at any position. Examples of such substituents include hydroxyl, alkoxy, acetoxy, and carbonyl groups.
[0100] Specific examples of the aforementioned substituted alkyl groups include 2-hydroxyethyl, 2-methoxycarbonylethyl, 2-acetoxyethyl, 2-(3-methoxycarbonylpropionyloxy)ethyl, and 3-hydroxypropyl.
[0101] Specific examples of the aforementioned aryl groups include phenyl, naphthyl, and hydroxyphenyl.
[0102] Specific examples of the aforementioned aralkyl groups include phenethyl, benzyl, and hydroxyphenylalkyl.
[0103] As a specific example of the aforementioned cycloalkyl groups, cyclohexyl can be cited.
[0104] R16 It can be a hydrogen atom, hydroxyl group, alkyl group, substituted alkyl group, aryl group, aralkyl group, group containing an ester bond, group containing an amino group, or group containing a 2,2,6,6-tetrasubstituted piperidinyl group. R 16 Two or more of these groups can be combined.
[0105] Specific examples of the aforementioned alkyl groups include methyl, ethyl, propyl, butyl, dodecyl, and stearyl.
[0106] The aforementioned substituted alkyl group is an alkyl group having a substituent at any position. Examples of such substituents include hydroxyl, alkoxy, acetoxy, and carbonyl groups.
[0107] Specific examples of the aforementioned substituted alkyl groups include 2-hydroxyethyl, 2-methoxycarbonylethyl, 2-acetoxyethyl, 2-(3-methoxycarbonylpropionyloxy)ethyl, and 3-hydroxypropyl.
[0108] Specific examples of the aforementioned aryl groups include phenyl and naphthyl groups.
[0109] Specific examples of the aforementioned aralkyl groups include phenethyl and benzyl.
[0110] Specific examples of the groups containing ester bonds mentioned above include acetoxy, propionyloxy, butyryloxy, lauroyloxy, substituted alkyl carbonyloxy, benzoyloxy, and substituted benzoyloxy.
[0111] Specific examples of the amino groups mentioned above include alkoxycarbonylamino, N-monoalkylcarbamoylamino, and N,N-dialkylcarbamoylamino.
[0112] Specific examples of compounds containing a piperidine group include 2,2,6,6-tetramethylpiperidine, 1,2,2,6,6-pentamethylpiperidine, 4-hydroxy-2,2,6,6-tetramethylpiperidine, 4-hydroxy-1,2,2,6,6-pentamethylpiperidine, 1-ethyl-2,2,6,6-tetramethylpiperidine, 1-ethyl-4-hydroxy-2,2,6,6-tetramethylpiperidine, 1-butyl-4-hydroxy-2,2,6,6-tetramethylpiperidine, 1-dodecyl-2,2,6,6-tetramethylpiperidine, 1-phenyl-2,2,6,6-tetramethylpiperidine, 1-(2-hydroxyethyl)-2,2,6,6-tetramethylpiperidine, 1-(6-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine, 4-acetoxy-2,2,6,6-tetramethylpiperidine, and 4-acetoxy-2,2,6,6-tetramethylpiperidine. -1,2,2,6,6-pentamethylpiperidine, 1-(2-acetoxyethyl)-4-acetoxy-2,2,6,6-tetramethylpiperidine, 1-(2-benzoyloxyethyl)-4-benzoyloxy-2,2,6,6-tetramethylpiperidine, 4-ethyl-2,2,6,6-tetramethylpiperidine, 4-ethyl-1,2,2,6,6-pentamethylpiperidine, 4-butyl-2,2,6 6-Tetramethylpiperidine, 4-octyl-2,2,6,6-tetramethylpiperidine, 4-dodecyl-2,2,6,6-tetramethylpiperidine, 4-stearyl-2,2,6,6-tetramethylpiperidine, 4-stearyl-1,2,2,6,6-pentamethylpiperidine, methyl 1,2,2,6,6-pentamethyl-4-piperidinyl sebacate, bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate.
[0113] As R 16 Compounds containing a piperidinyl group, which contain a 2,2,6,6-tetramethylpiperidinyl group, can be listed as such. Examples include compounds containing a piperidinyl group, obtained by reacting 2,2,6,6-tetramethylpiperidin (4-hydroxy-2,2,6,6-tetramethylpiperidin, 4-hydroxy-1,2,2,6,6-pentamethylpiperidin, 1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidin, 1-(2-hydroxyethyl)-2,2,6,6-tetramethylpiperidin, etc.) with a polybasic acid (succinic acid, adipic acid, sebacic acid, azelaic acid, decane-1,10-dicarboxylic acid, phthalic acid, isophthalic acid, terephthalic acid, trimellitic acid, malonic acid, substituted malonic acid, etc.) with a hydroxyl group. Specifically, compounds with the following formulas can be listed.
[0114] Where n3 is an integer from 1 to 20. Additionally, in the following compounds, n refers to a positive value.
[0115]
[0116] The content of the piperidine-containing compound relative to the total mass of the solid composition is preferably 0.01 to 3.0% by mass, more preferably 0.05 to 2.0% by mass, even more preferably 0.1 to 2.0% by mass, and particularly preferably 0.1 to 1.7% by mass. If the content of the piperidine-containing compound is 0.01% by mass or more, the lightfastness of the coating film is superior. Furthermore, if the content of the piperidine-containing compound is 3.0% by mass or less, the impact resistance is superior.
[0117] Ethylbenzene can be a polymerization solvent used in the manufacture of a specific fluorinated copolymer, or it can be a substance added independently of the aforementioned polymerization solvent in the manufacture of this solid composition.
[0118] Here, the standard boiling point of ethylbenzene is 136°C. It should be noted that in this specification, the standard boiling point refers to the boiling point at 1 atm.
[0119] The content of ethylbenzene relative to the total mass of the solid composition is preferably 0.01 to 0.3% by mass, more preferably 0.02 to 0.3% by mass, even more preferably 0.03 to 0.2% by mass, and particularly preferably 0.04 to 0.15% by mass. If the content of ethylbenzene is 0.01% by mass or more, the lightfastness of the coating film is superior. Furthermore, if the content of ethylbenzene is 0.3% by mass or less, the resistance to clogging is superior.
[0120] In this solid composition, the mass ratio of the content of the piperidinyl compound to the content of ethylbenzene (content of the piperidinyl compound / content of ethylbenzene) is preferably 0.5 to 200, more preferably 0.5 to 170, further preferably 1.0 to 100, and particularly preferably 1.0 to 50.
[0121] If the above mass ratio is 0.5 or higher, the coating film exhibits superior lightfastness and impact resistance. If the above mass ratio is 200 or lower, the coating film demonstrates superior durability.
[0122] Mixed xylenes refer to a mixture of xylene structural isomers including o-xylene, m-xylene, and p-xylene. Mixed xylenes are mixed xylenes containing at least two of o-xylene, m-xylene, and p-xylene, preferably containing all of o-xylene, m-xylene, and p-xylene. The mixed xylenes can be a polymerization solvent used in the manufacture of a specific fluorinated copolymer, or a polymerization solvent added independently of the aforementioned polymerization solvents in the manufacture of this solid composition.
[0123] Here, the standard boiling points of o-xylene, m-xylene, and para-xylene are 144℃, 139℃, and 138℃, respectively.
[0124] The content of the mixed xylene relative to the total mass of the solid composition is preferably 0.02 to 0.4% by mass, more preferably 0.03 to 0.3% by mass, and even more preferably 0.05 to 0.2% by mass. If the content of the mixed xylene is 0.02% by mass or more, the impact resistance of the coating film is better. In addition, if the content of the mixed xylene is 0.4% by mass or less, the anti-blocking property is better.
[0125] The content of o-xylene relative to the total mass of the mixed xylenes is preferably 30-60% by mass, more preferably 40-50% by mass.
[0126] In this solid composition, the mass ratio of ethylbenzene content to mixed xylene content (ethylbenzene content / mixed xylene content) is preferably 0.1 to 7.0, more preferably 0.2 to 4.0, further preferably 0.2 to 1.5, particularly preferably 0.4 to 1.0, and most preferably 0.5 to 0.8.
[0127] If the above mass ratio is 0.1 or higher, the coating film exhibits superior impact resistance. If the above mass ratio is 7.0 or lower, the coating film exhibits superior resistance to adhesion.
[0128] This solid composition may contain other components besides those described above (hereinafter also referred to as other components).
[0129] Specific examples of other components include solvents other than ethylbenzene and mixed xylenes (hereinafter also referred to as other solvents).
[0130] When this solid composition contains other components, from the viewpoint of achieving better impact resistance and smoothness of the coating, the content of the other components relative to the total mass of this solid composition is preferably 0.01 to 0.2% by mass, more preferably 0.02 to 0.1% by mass.
[0131] Other examples of solvents include organic solvents such as alcohols (e.g., ethanol) and cyclohexanone.
[0132] When this solid composition contains other solvents, from the viewpoint of superior impact resistance and smoothness of the coating film, the content of other solvents is preferably more than 0% by mass and less than 0.2% by mass relative to the total mass of this solid composition, more preferably 0.02 to 0.1% by mass. The total content of ethylbenzene, mixed xylenes, and other solvents is less than 3% by mass relative to the total mass of this solid composition.
[0133] From the viewpoint that the air removal is good during the manufacture of the solid composition and the drying of the coating layer, and that the resulting coating film has excellent impact resistance, the standard boiling point of the solvent contained in the solid composition is preferably 120 to 150°C, more preferably 130 to 150°C, and even more preferably 135 to 145°C.
[0134] This solid composition is preferably used as a raw material for powder coatings. In this specification, the solid composition used as a raw material for powder coatings will also be referred to as a solid composition for powder coatings.
[0135] This solid composition is sometimes used after being redissolved in a solvent.
[0136] The method of manufacturing this solid composition is not particularly limited, but examples such as the following methods can be listed.
[0137] As one embodiment of the method for manufacturing this solid composition, an embodiment including the following steps can be listed:
[0138] Step 1 involves polymerizing a monomer containing trifluorochloroethylene and vinyl ether in the presence of a polymerization solvent, a piperidine-containing compound, and a free radical polymerization initiator to produce a solution containing a fluorinated copolymer, the aforementioned polymerization solvent, and the aforementioned piperidine-containing compound, wherein the polymerization solvent contains ethylbenzene and a mixture of xylenes containing o-xylene, m-xylene, and p-xylene.
[0139] Step 2 involves removing at least a portion of the polymerization solvent from the solution to obtain a solid composition comprising the fluorinated copolymer, the piperidine-containing compound, ethylbenzene, and the mixed xylenes.
[0140] The polymerization solvent comprises a mixture of xylene and ethylbenzene. The mixed xylene is suitable in the same manner as described above in this solid composition.
[0141] When a solid composition is obtained by removing the polymerization solvent, an air passage corresponding to the boiling point of the vaporized component is formed in stages, thereby improving the removal of air and the performance of the subsequent powder coating. From this point of view, the mass ratio of the amount of ethylbenzene to the amount of mixed xylene (amount of ethylbenzene / amount of mixed xylene) is preferably 0.2 to 4.0, more preferably 0.5 to 2.0, and even more preferably 0.7 to 1.4.
[0142] From the viewpoint of excellent coating durability, the total amount of mixed xylene and ethylbenzene relative to the total amount of polymerization solvent (the total amount of all polymerization solvents used in the polymerization) is preferably 50 to 100% by mass, more preferably 70 to 100% by mass.
[0143] The polymerization solvent may include solvents other than the mixture of xylene and ethylbenzene (hereinafter also referred to as other solvents). Other solvents are suitable in the same manner as described above in this solid composition.
[0144] When using other solvents, from the viewpoint of excellent coating durability, the amount of other solvents used relative to the total amount of polymerizing solvent is preferably 10 to 50% by mass, more preferably 20 to 30% by mass.
[0145] Compounds containing piperidine groups are suitable in the same manner as described in the above description of this solid composition.
[0146] From the viewpoint of stability in the polymerization process and lightfastness of the coating, the molar amount of piperidinium in the piperidinium-containing compound relative to the molar amount of the total monomers used (the total molar amount of all monomers used in the polymerization) is preferably 0.0001 to 0.010, more preferably 0.0002 to 0.005, and even more preferably 0.0002 to 0.0038.
[0147] The monomers comprise trifluorochloroethylene and vinyl ethers. The trifluorochloroethylene and vinyl ethers are suited in the same manner as described in the specific fluorinated copolymers above.
[0148] The appropriate method for the amount of trifluorochloroethylene relative to the total amount of monomer is the same as the appropriate method for the amount of trifluorochloroethylene-based units relative to the content of all repeating units of the aforementioned specific fluorinated copolymer.
[0149] Furthermore, the suitable methods for the amount of vinyl ether, vinyl ether with crosslinking groups, and vinyl ether without crosslinking groups relative to the total amount of monomers used in this manufacturing method are the same as the suitable methods for the content of vinyl ether-based units, the content of vinyl ether with crosslinking groups, and the content of vinyl ether without crosslinking groups relative to all repeating units of the aforementioned specific fluorinated copolymer.
[0150] In this manufacturing method, monomers other than trifluorochloroethylene and vinyl ether can be used. From the viewpoint of further improving the lightfastness of the coating film, it is preferable to use only trifluorochloroethylene and vinyl ether as monomers.
[0151] In this manufacturing method, it is preferable to use a monomer that contains trifluorochloroethylene, a vinyl ether with crosslinking groups, and a vinyl ether without crosslinking groups; more preferably, a monomer that contains only trifluorochloroethylene, a vinyl ether with crosslinking groups, and a vinyl ether without crosslinking groups is used.
[0152] The appropriate manner in which the amounts of trifluorochloroethylene, vinyl ethers with crosslinking groups, and vinyl ethers without crosslinking groups are used relative to the total amount of monomers is the same as the appropriate manner in which the amounts of trifluorochloroethylene-based units, vinyl ether-based units, and vinyl ether-based units without crosslinking groups are used relative to all units contained in the aforementioned specific fluorinated copolymer.
[0153] From the viewpoint of improving the durability of the coating, the mass ratio of the total amount of monomer to the total amount of polymerization solvent (total amount of monomer / total amount of polymerization solvent) is preferably 1.0 to 3.0, and more preferably 1.3 to 2.5.
[0154] Peroxide initiators and azo initiators can be listed as examples of free radical polymerization initiators.
[0155] Specific examples of peroxide-based initiators include cyclohexanone peroxide, tert-butyl hydroperoxide, benzoyl peroxide, di-tert-butyl peroxide, 2,2-di(tert-butyl peroxide)butane, tert-butyl peroxypentanoate, and diisopropyl peroxydicarbonate.
[0156] Specific examples of azo initiators include 2,2'-azobisisobutyronitrile, 2,2'-azobiscyclohexaneformitrile, 2,2'-azobis(2,4-dimethylpentanonitrile), and 2,2'-azobis(2-methylbutyronitrile).
[0157] Two or more free radical polymerization initiators can be used in combination.
[0158] The molar ratio of the free radical polymerization initiator to the total amount of monomer is preferably 0.0005 to 0.01, more preferably 0.001 to 0.005.
[0159] In step 1, hydrotalcite can be used. Hydrotalcite refers to a layered double hydroxide as shown in the following formula.
[0160] [Mg 2+ 1-x Al 3+ x (OH)2] x+ CO3 2- x / 2 ·mH2O] x-
[0161] In the formula, x is 0.2 to 0.33 and m is 0 to 2.
[0162] From the perspectives of excellent chloride ion adsorption and easy availability, hydrotalcite is preferably Mg6Al2(OH). 16 CO3·4H2O (in the above formula representing hydrotalcite, x = 0.25, m = 0.5) or Mg 4.5 Al2(OH) 13 CO3·3.5H2O (in the above formula representing hydrotalcite, x = 0.308 and m = 0.538).
[0163] Two or more types of hydrotalcite can be used.
[0164] The particle size of the hydrotalcite is preferably 5–500 μm, more preferably 5–110 μm. If the particle size of the hydrotalcite is 5 μm or larger, it is easily removed by filtration. If the particle size of the hydrotalcite is 500 μm or smaller, the surface area per unit mass is large, further enhancing the effect achieved by the hydrotalcite.
[0165] The particle size of hydrotalcite was determined according to JIS K 0069, "Sieve test method for chemical products".
[0166] When using hydrotalcite, the mass ratio of hydrotalcite to the total amount of monomers (the total amount of all monomers used in the polymerization) is preferably 0.001 to 0.050, more preferably 0.003 to 0.030. If the above ratio is within the above range, the molecular weight distribution of the resulting fluorinated copolymer can be further reduced.
[0167] When using hydrotalcite, the mass ratio of the amount of hydrotalcite to the amount of the compound containing piperidinyl group is preferably 0.30 or more and less than 4.60, more preferably 0.50 to 3.00, and even more preferably 1.0 to 2.0.
[0168] In step 1, after the polymerization of monomers containing trifluorochloroethylene and vinyl ether begins, trifluorochloroethylene and vinyl ether are continuously or intermittently supplied to the reaction system.
[0169] Therefore, during the polymerization reaction, the concentrations of trifluorochloroethylene and vinyl ether in the reaction system tend to remain constant, thus enabling the production of fluorinated copolymers with more uniform molecular weights.
[0170] A reaction system refers to a system containing trifluorochloroethylene and vinyl ethers that has undergone a polymerization reaction, such as one present in a reactor.
[0171] In this manufacturing method, after the polymerization of the monomers begins, a mixture of trifluorochloroethylene and vinyl ether can be supplied to the reaction system, or trifluorochloroethylene and vinyl ether can be supplied to the reaction system separately. Alternatively, after the polymerization of the monomers begins, monomers other than trifluorochloroethylene and vinyl ether can be supplied to the reaction system either as a mixture with at least one of trifluorochloroethylene and vinyl ether, or separately with trifluorochloroethylene and vinyl ether.
[0172] In step 1, a monomer containing, for example, trifluorochloroethylene and vinyl ether, a compound containing piperidinium, hydrotalcite as needed, and a free radical polymerization initiator are added into the reactor, and polymerization begins.
[0173] When the amount of trifluorochloroethylene added before the start of polymerization (hereinafter also referred to as the initial stage) is a portion of the total amount of trifluorochloroethylene used in the polymerization reaction, the remainder is used for continuous or intermittent supply to the reaction system after the start of polymerization (hereinafter also referred to as continuous addition). Similarly, when the amount of vinyl ether added in the initial stage is a portion of the total amount of vinyl ether used in the polymerization reaction, the remainder is used for continuous addition after the start of polymerization.
[0174] Regarding compounds containing piperidine groups, the entire amount used in this manufacturing method can be added initially, or a portion of the entire amount used in this manufacturing method can be added initially, with the remainder added to the reaction system after polymerization begins. Preferably, the entire amount of the piperidine-containing compound is added initially. When adding the piperidine-containing compound to the reaction system after polymerization begins, it can be added continuously or all at once.
[0175] When using hydrotalcite, the hydrotalcite can be added in its entirety initially, or a portion thereof initially, with the remainder added to the reaction system after polymerization begins. It is preferable to add the entire amount of hydrotalcite initially. When adding the hydrotalcite to the reaction system after polymerization begins, it can be added continuously or all at once.
[0176] Regarding the free radical polymerization initiator, it can be added in the entire amount used in the polymerization of the monomer at the beginning, or a portion of the entire amount used in the polymerization of the monomer at the beginning, with the remainder added to the reaction system after polymerization begins. Preferably, a portion of the entire amount used in the polymerization of the monomer is added at the beginning, with the remainder added to the reaction system after polymerization begins; more preferably, a portion of the entire amount used in the polymerization of the monomer is added at the beginning, with the remainder continuously added to the reaction system after polymerization begins.
[0177] The polymerization solvent is preferably added to the reactor along with the monomer before polymerization begins.
[0178] In step 1, the temperature inside the reactor during monomer polymerization (polymerization temperature) is preferably 50–90°C, more preferably 60–80°C. The polymerization temperature is the temperature inside the reaction system at the start of polymerization, and is the temperature inside the reaction system when additional monomers are continuously added and polymerized after the start of polymerization.
[0179] The pressure (hereinafter also referred to as polymerization pressure) in the reaction system when additional monomers containing trifluorochloroethylene and vinyl ether are continuously added after the start of polymerization is preferably 0.3 to 0.8 MPa, more preferably 0.4 to 0.7 MPa.
[0180] Furthermore, the polymerization time from the start of monomer polymerization to the end of polymerization of monomers with continuously added additional monomers is preferably 0.5 to 30 hours, more preferably 1 to 5 hours.
[0181] In step 1, chain transfer agents, polymerization inhibitors, stabilizers, and other components may be used as needed.
[0182] When hydrotalcite is used in step 1, a mixture containing insoluble components derived from hydrotalcite can be obtained after the polymerization of the monomers. In this case, step 1 may also include a process for removing the insoluble components from the mixture.
[0183] Specific examples of methods for removing insoluble components include solid-liquid separation processes such as filtration.
[0184] In step 1, after the monomer is polymerized according to the above steps, a solution (hereinafter also referred to as a specific solution) is obtained containing the fluorinated copolymer, the above-mentioned polymerization solvent and the above-mentioned piperidine-containing compound.
[0185] The fluorinated copolymer obtained through step 1 is the same as the specific fluorinated copolymer in the above solid composition, and is suitable in the same manner. Therefore, the fluorinated copolymer contained in the specific solution is also referred to as the specific fluorinated copolymer.
[0186] The content of the specific fluorinated copolymer relative to the total mass of the specific solution is preferably 30-80% by mass, more preferably 40-70% by mass.
[0187] From the viewpoint of improving the durability of the coating, the content of the polymer solvent relative to the total mass of the specific solution is preferably 20 to 70% by mass, more preferably 30 to 60% by mass.
[0188] From the viewpoint of improving the durability of the coating, the content of ethylbenzene relative to the total mass of the specific solution is preferably 5 to 40% by mass, more preferably 10 to 28% by mass.
[0189] From the viewpoint of improving the durability of the coating, the content of mixed xylene relative to the total mass of the specific solution is preferably 5 to 40% by mass, more preferably 10 to 28% by mass.
[0190] From the viewpoint of further improving the lightfastness of the coating, the content of the piperidine-containing compound relative to the total mass of the specific solution is preferably 0.01 to 2.0% by mass, more preferably 0.05 to 1.5% by mass.
[0191] In step 2, at least a portion of the polymerization solvent is removed from the specific solution. Specific examples of methods for removing the polymerization solvent from the specific solution include heating and distillation.
[0192] Step 2 is preferably carried out under the condition that the content of the polymerization solvent contained in the solid composition obtained by step 2 is more than 0% by mass and less than 3% by mass relative to the total mass of the solid composition.
[0193] In step 2, after removing at least a portion of the above-mentioned polymerization solvent from a specific solution, a solid composition comprising a specific fluorinated copolymer, a compound containing piperidine, ethylbenzene, and mixed xylenes is obtained.
[0194] The solid composition obtained through step 2 is the same as the solid composition described above, and the suitable method is also the same.
[0195] The powder coating of the present invention (hereinafter also referred to as the coating) comprises: a specific fluorinated copolymer contained in the solid composition, a compound containing piperidine, ethylbenzene, and a mixture of xylenes containing o-xylene, m-xylene and p-xylene.
[0196] From the viewpoint of further improving the lightfastness and impact resistance of the coating film, the content of the specific fluorinated copolymer is preferably 30 to 60% by mass relative to the total mass of the coating, and more preferably 40 to 55% by mass.
[0197] From the viewpoint of further improving the lightfastness and impact resistance of the coating film, the content of the piperidine-containing compound relative to the total mass of the coating is preferably 0.02 to 2.0% by mass, more preferably 0.05 to 1.0% by mass.
[0198] From the viewpoint of further improving the lightfastness and impact resistance of the coating film, the content of ethylbenzene relative to the total mass of the coating is preferably 0.005 to 0.11% by mass, more preferably 0.02 to 0.07% by mass.
[0199] From the viewpoint of further improving the lightfastness and impact resistance of the coating film, the content of mixed xylene relative to the total mass of the coating is preferably 0.01 to 0.15% by mass, more preferably 0.02 to 0.11% by mass.
[0200] This coating may also contain additives.
[0201] Specific examples of additives include pigments, curing agents, catalysts (curing catalysts, etc.), polymers other than those mentioned above (e.g., polyester resins, (meth)acrylic resins, epoxy resins), fillers (resin beads, etc.), light stabilizers, ultraviolet absorbers, matting agents, surface conditioners, degassing agents, flow agents, heat stabilizers, antistatic agents, rust inhibitors, silane coupling agents, low-pollution treatment agents, plasticizers, adhesives, etc.
[0202] From the viewpoint of further improving the lightfastness and impact resistance of the coating film, the content of solvent contained in this coating is preferably 1% by mass or less, more preferably 5000 ppm by mass or less, and even more preferably 2000 ppm by mass or less.
[0203] The solvent content in this coating is preferably 200 ppm by mass or more, more preferably 300 ppm by mass or more, and even more preferably 400 ppm by mass or more.
[0204] It should be noted that ethylbenzene and mixed xylenes are classified as solvents.
[0205] This coating can be manufactured by mixing this solid composition with additives as needed. The mixed solid composition and additives can be in separate powder or granule form.
[0206] One method for manufacturing this coating is to melt-mix the solid composition and additives as needed, cool them, and then pulverize them to obtain a powder coating. The melt-mixing temperature is preferably below the standard boiling points of ethylbenzene, o-xylene, m-xylene, and p-xylene, and more preferably 80–130°C.
[0207] Another method for manufacturing this coating is to mix the powder of this solid composition with powder of additives used as needed to obtain a powder coating. This method is also known as dry mixing, which is a method in which no melt mixing is performed during mixing.
[0208] The pulverization can be performed using a pin mill, hammer mill, or spray mill. Preferably, after pulverization, the pulverized material is classified and the resulting powder coating has a uniform particle size. The average particle size of the powder coating is preferably 1–100 μm, more preferably 10–80 μm.
[0209] The coating of the present invention (hereinafter also referred to as the coating) is formed by supplying the coating onto a substrate.
[0210] Furthermore, the coated article of the present invention has a substrate and a coating film, the coating film being disposed on the substrate and formed by the coating material.
[0211] Specific examples of materials that can be used as substrates include inorganic materials, organic materials, and organic-inorganic composite materials.
[0212] Specific examples of inorganic materials include concrete, natural stone, glass, and metals (iron, stainless steel, aluminum, copper, brass, titanium, etc.).
[0213] Specific examples of organic materials include plastics, rubber, adhesives, and wood.
[0214] Specific examples of organic-inorganic composite materials include fiber-reinforced plastics, resin-reinforced concrete, and fiber-reinforced concrete.
[0215] In addition, the substrate can undergo known surface treatments (chemical forming treatments, etc.). Furthermore, a resin layer (polyester resin layer, acrylic resin layer, silicone resin layer, etc.) formed by applying a primer or similar material can be pre-formed on the surface of the substrate.
[0216] The preferred material for the substrate is metal, more preferably iron, iron-containing alloys (e.g., carbon steel, stainless steel), or aluminum.
[0217] Specific examples of the shape of the substrate include flat plate, spherical, and rod-shaped.
[0218] The thickness of this coating is preferably 20 to 1,000 μm, more preferably 20 to 500 μm.
[0219] When conducting a lightfastness test on this coating, from the viewpoint of superior lightfastness, the 60° gloss retention rate of this coating is preferably 90% or more, and more preferably 95% or more.
[0220] Here, 60° gloss retention rate refers to the ratio (in %) of the 60° gloss value of the coating before the lightfastness test (set to 100%) to the 60° gloss value of the coating after the lightfastness test. The conditions for the lightfastness test and the method for determining the 60° gloss are as described in the Examples section below.
[0221] When conducting an impact resistance test on this coating, the drop height at which the coating does not exhibit any abnormalities (specifically, cracking or peeling) is preferably 25 cm or more, more preferably 30 cm or more, and even more preferably 35 cm or more.
[0222] Here, the conditions for the impact resistance test are as described in the Examples section below.
[0223] The coated article of the present invention is preferably manufactured by supplying (applying) the coating to the surface of a substrate to form a coating layer, heating the resulting coating layer, and then cooling it.
[0224] Methods for forming coating layers include electrostatic coating, electrostatic spraying, electrostatic impregnation, flow impregnation, and spraying, with electrostatic coating using a powder coating gun being the preferred method.
[0225] Specific examples of powder coating guns include corona-charged coating guns and triboelectric coating guns. A corona-charged coating gun is a coating gun that sprays powder coatings after applying a corona discharge treatment. A triboelectric coating gun is a coating gun that sprays powder coatings after applying a triboelectric charge treatment.
[0226] The preferred heating temperature during heat treatment is 120–250°C. The heating duration is typically 2–60 minutes. After heat treatment, it is preferable to cool to 20–25°C. Through heat treatment and cooling, the coating layer melts and solidifies (melt-solidification), forming the coating film.
[0227] Example
[0228] The present invention will be described in detail below with examples. Examples 1 to 7 are exemplary embodiments, and Examples 8 to 10 are comparative examples. The present invention is not limited to these examples. It should be noted that the mixing amounts of each component in the following tables represent quality standards unless otherwise specified.
[0229] [Synthesis example 1]
[0230] Add 20g of a piperidinyl compound (BASF, trade name "TINUVIN292"), a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and methyl 1,2,2,6,6-pentamethyl-4-piperidinyl sebacate (mass ratio 3:1) and 20g of hydrotalcite (Kyowa Chemical Industry Co., Ltd., trade name "KW500", particle size 4) to a 2500ml stainless steel pressure reactor equipped with a stirrer. The following components were used: 38% of particles smaller than 5 μm, 35% of particles 45–75 μm, 21% of particles 75–106 μm, and 6% of particles 106–500 μm; 285 g of ethylbenzene; 394 g of mixed xylenes (a mixture of o-xylene, m-xylene, and p-xylene); 118 g of 4-hydroxybutyl vinyl ether (hereinafter also referred to as HBVE); and 453 g of cyclohexyl vinyl ether (hereinafter also referred to as CHVE). Dissolved oxygen in the liquid was removed by nitrogen-based degassing. Then, 536 g of trifluorochloroethylene (hereinafter also referred to as CTFE) was introduced into the reactor and the temperature was raised. The temperature inside the reactor was raised to 65°C. Subsequently, 2 ml of a 5% xylene solution of tert-butyl peroxypentanoate (hereinafter also referred to as PBPV) was added to the reactor to start the reaction.
[0231] While maintaining the reaction rate, 110 g of CTFE, 93 g of CHVE, and 24 g of HBVE monomers were continuously added to the reactor, and a 5% xylene solution of PBPV as a free radical polymerization initiator was intermittently added to the reactor to carry out polymerization. After the polymerization started, the total amount of the 5% xylene solution of PBPV added to the reactor intermittently was 55 ml. After 16 hours, the reactor was water-cooled to stop the reaction.
[0232] After cooling the reaction solution to room temperature (23°C, the same applies below), unreacted monomers were purged, and insoluble components of the resulting reaction solution were removed by filtration to obtain solution 1 containing fluorinated copolymer 1. The composition of solution 1 is shown in Table 1.
[0233] The composition of fluorinated copolymer 1 is CTFE unit / HBVE unit / CHVE unit = 50 / 11 / 39 (molar ratio).
[0234] It should be noted that mixed xylenes include para-xylene, but in Tables 1-3, when using mixed xylenes, the content of para-xylene is not recorded and is left blank.
[0235] [Synthesis example 2]
[0236] 8.6 g of a piperidinyl compound (BASF, trade name "Tinuvin 292"), a mixture of bis(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate and methyl 1,2,2,6,6-pentamethyl-4-piperidinyl sebacate (mass ratio 3:1) and 17 g of hydrotalcite (Kyowa Chemical Industry Co., Ltd., trade name "KW500") were added to a 2500 ml stainless steel pressure reactor equipped with a stirrer. The following components were used: 38% of particles with a diameter of less than 45 μm, 35% of particles with a diameter of 45–75 μm, 21% of particles with a diameter of 75–106 μm, and 6% of particles with a diameter of 106–500 μm; 493 g of ethylbenzene; 357 g of mixed xylenes (a mixture of o-xylene, m-xylene, and p-xylene); 196 g of ethyl vinyl ether (hereinafter also referred to as EVE); 123 g of HBVE; and 198 g of CHVE. Dissolved oxygen in the liquid was removed by nitrogen-based degassing. Then, 629 g of CTFE was introduced into the reactor and the temperature was raised. The reactor temperature was increased to 65°C. Subsequently, 2 ml of a 20% xylene solution of PBPV was added to the reactor to initiate the reaction.
[0237] Subsequently, a 20% xylene solution of PBPV, acting as a free radical polymerization initiator, was intermittently added to the reactor to initiate polymerization. The total amount of the 20% xylene solution of PBPV added to the reactor intermittently after the start of polymerization was 50 ml. The reaction was stopped by water cooling the reactor after 16 hours.
[0238] After cooling the reaction solution to room temperature, unreacted monomers were purged, and insoluble components in the resulting reaction solution were removed by filtration to obtain a solution containing fluorinated copolymer 2. The composition of solution 2 is shown in Table 1.
[0239] The composition of fluorinated copolymer 2 is CTFE unit / EVE unit / HBVE unit / CHVE unit = 50 / 25 / 10 / 15 (molar ratio).
[0240] [Synthesis example 3]
[0241] 12g of potassium carbonate, 142g of ethanol, 262g of ethylbenzene, 241g of mixed xylenes (a mixture of o-xylene, m-xylene, and p-xylene), 85g of HBVE, and 327g of CHVE were added to a 2500ml stainless steel pressure reactor equipped with a stirrer. Dissolved oxygen in the liquid was removed by nitrogen-based degassing. Then, 387g of CTFE was introduced into the reactor and the temperature was raised to 65°C. Subsequently, 5ml of a 10% xylene solution of PBPV was added to the reactor to initiate the reaction.
[0242] While maintaining the reaction rate, 273 g of CTFE, 231 g of CHVE, and 60 g of HBVE monomers were continuously added to the reactor, and a 10% xylene solution of PBPV as a free radical polymerization initiator was intermittently added to the reactor to carry out polymerization. After the polymerization started, the total amount of the 10% xylene solution of PBPV added to the reactor intermittently was 61 ml. After 16 hours, the reactor was water-cooled to stop the reaction.
[0243] After cooling the reaction solution to room temperature, 3 g of hydroquinone monomethyl ether (hereinafter also referred to as HQMME) was added, unreacted monomers were purged, and insoluble components in the resulting reaction solution were removed by filtration. Ethanol was then removed by vacuum distillation. Additionally, 4.1 g of a piperidinyl compound (manufactured by BASF, trade name "Tinuvin 144") was added and stirred until dissolved to obtain a solution containing fluorinated copolymer 3. The composition of solution 3 is shown in Table 1.
[0244] The composition of fluorinated copolymer 3 is CTFE unit / HBVE unit / CHVE unit = 51 / 10 / 39 (molar ratio).
[0245] [Synthesis Example 4]
[0246] 11g of potassium carbonate, 168g of ethanol, 276g of ethylbenzene, 311g of mixed xylenes (a mixture of o-xylene, m-xylene, and p-xylene), 206g of EVE, 129g of HBVE, and 208g of CHVE were added to a 2500ml stainless steel pressure reactor equipped with a stirrer. Dissolved oxygen in the liquid was removed by nitrogen-based degassing. Then, 660g of CTFE was introduced into the reactor and the temperature was raised. The pressure was 0.58 MPaG when the temperature inside the reactor reached 65°C. Subsequently, 2ml of a 20% xylene solution of PBPV was added to the reactor to initiate the reaction.
[0247] Subsequently, a 20% xylene solution of PBPV as a free radical polymerization initiator was intermittently added to the reactor to carry out polymerization. The total amount of the 20% xylene solution of PBPV added to the reactor intermittently after the start of polymerization was 50 ml. The reaction was stopped by water cooling the reactor after 16 hours.
[0248] After cooling the reaction solution to room temperature, 0.1 g of HQMME was added to purge unreacted monomers. The insoluble components of the resulting reaction solution were removed by filtration, and then ethanol was removed by vacuum distillation. Additionally, 1.2 g of Tinuvin 144 was added and stirred until dissolved to obtain a solution containing fluorinated copolymer 4. The composition of solution 4 is shown in Table 1.
[0249] The composition of fluorinated copolymer 4 is CTFE unit / EVE unit / HBVE unit / CHVE unit = 51 / 25 / 10 / 14 (molar ratio).
[0250] [Synthesis example 5]
[0251] 10g of potassium carbonate, 156g of ethanol, 343g of ethylbenzene, 280g of mixed xylenes (a mixture of o-xylene, m-xylene, and p-xylene), 26g of EVE, 55g of HBVE, and 44g of CHVE were added to a 2500ml stainless steel pressure reactor equipped with a stirrer. Dissolved oxygen in the liquid was removed by nitrogen-based degassing. Then, 171g of CTFE was introduced into the reactor and the temperature was raised to 65°C. Subsequently, 5ml of a 25% xylene solution of PBPV was added to the reactor to initiate the reaction.
[0252] While maintaining the reaction rate, additional monomers of 457g CTFE, 87g EVE, 149g CHVE, and 183g HBVE were continuously added to the reactor. Simultaneously, a 25% xylene solution of PBPV was intermittently added to the reactor as a free radical polymerization initiator. After polymerization began, the total amount of the 25% xylene solution of PBPV added to the reactor intermittently was 30ml. The reaction was stopped after 16 hours by water cooling of the reactor.
[0253] After cooling the reaction solution to room temperature, 0.1 g of HQMME was added to purge unreacted monomers. The insoluble components of the resulting reaction solution were removed by filtration, and then ethanol was removed by vacuum distillation. Additionally, 3.5 g of Tinuvin 144 was added and stirred until dissolved to obtain a solution containing fluorinated copolymer 5. The composition of solution 5 is shown in Table 1.
[0254] The composition of fluorinated copolymer 5 is CTFE unit / EVE unit / HBVE unit / CHVE unit = 51 / 15 / 19 / 15 (molar ratio).
[0255] [Synthesis Examples 6 to 9]
[0256] By changing the type or composition of the solvent used as shown in Table 1, and otherwise operating in the same manner as in Synthesis Example 1, solutions 6 containing fluoropolymer 6, 7 containing fluoropolymer 7, 8 containing fluoropolymer 8, and 9 containing fluoropolymer 9 were obtained. The compositions of solutions 6 to 9 are shown in Table 1.
[0257] The composition of fluorinated copolymer 6 is CTFE unit / HBVE unit / CHVE unit = 51 / 9 / 40 (molar ratio).
[0258] The composition of fluorinated copolymer 7 is CTFE unit / HBVE unit / CHVE unit = 50 / 11 / 39 (molar ratio).
[0259] The composition of fluorinated copolymer 8 is CTFE unit / HBVE unit / CHVE unit = 51 / 10 / 39 (molar ratio).
[0260] The composition of fluorinated copolymer 9 is CTFE unit / HBVE unit / CHVE unit = 51 / 11 / 38 (molar ratio).
[0261] [Synthesis Example 10]
[0262] Without the addition of Tinuvin 144, the procedure was the same as in Synthesis Example 3, yielding solution 10 containing the fluorinated copolymer 10. The composition of solution 10 is shown in Table 1.
[0263] The composition of fluorinated copolymer 10 is CTFE unit / HBVE unit / CHVE unit = 50 / 11 / 39 (molar ratio).
[0264] [Table 1]
[0265]
[0266] [Preparation of solid compositions]
[0267] Using a vacuum dryer, at least a portion of the solvent in each solution was removed by distillation. The solutions were dried under full vacuum for 3 hours at a dryer temperature of 65°C. Subsequently, they were dried under full vacuum for 20 minutes at a dryer temperature of 130°C to obtain solid compositions A-1 to A-5 and B-1 to B-5. The composition of each solid composition is shown in Table 2.
[0268] The content of each component in each solid composition was determined by the following procedure.
[0269] The contents of ethylbenzene, mixed xylenes, and p-xylenes were determined using a gas chromatograph (hereinafter also referred to as GC) apparatus, by the internal standard method, and according to the following steps.
[0270] The content of compounds containing piperidine groups was determined using liquid chromatography-mass spectrometry (LC-MS) with liquid chromatography-Fourier transform mass spectrometry, following the steps below.
[0271] It should be noted that the value obtained by subtracting the total content (in mass%) of ethylbenzene, mixed xylene, p-xylene, and compounds containing piperidine groups in the solid composition from the content (100% by mass) of the solid composition is set as the content of the fluorinated copolymer.
[0272] <Content of ethylbenzene, mixed xylenes, and p-xylene>
[0273] Prepare each solid composition, and add 200 parts by mass of acetone to 100 parts by mass of the solid composition to prepare a diluted solution of the solid composition.
[0274] Next, toluene, at a concentration of 1% by mass relative to the total mass of the diluent, was added to the aforementioned diluent to prepare a sample solution. As will be described later, in the GC determination, toluene was added as a reference for extracting peaks of trace components contained in the solid composition.
[0275] Next, the resulting sample solution was used to perform GC determination. The GC determination was performed using a gas chromatograph (detector: FID) manufactured by Agilent Technologies, under the following conditions.
[0276] (Sample injection volume) 1.0 μL
[0277] (Injection Mode) Flow Splitting
[0278] (Carrier gas) He
[0279] (Injection port temperature) 240℃
[0280] (Pressure) 199.9 kPa
[0281] (Total flow rate) 179 mL / min
[0282] (Split ratio) 100:1
[0283] (Shunting flow rate) 174 mL / min
[0284] (Column) Capillary column DB1301, length 60m × inner diameter 0.25mm, film thickness 1.00μm
[0285] (Column pressure) 199.9 kPa
[0286] (Column flow rate) 1.7 mL / min
[0287] (Average linear velocity) 29.0 cm / s
[0288] (Column oven temperature program) Hold at 40℃ for 10 minutes, then increase the temperature at 10℃ / minute and hold at 250℃ for 25 minutes.
[0289] (Detector) Flame Ionization Detection (FID)
[0290] (Detector temperature) 250℃
[0291] Next, the content of each solvent is calculated using the following formula.
[0292] The content of each solvent = (peak area of each solvent ÷ peak area of toluene) × factor of each solvent × mass of toluene ÷ mass of solid composition × 100
[0293] <Content of compounds containing piperidine>
[0294] A mixed standard of 1000 ppm of Tinuvin 144 and Tinuvin 292 was prepared using tetrahydrofuran (hereinafter also referred to as THF).
[0295] Next, the above mixed standard at 1000 ppm was diluted with THF to prepare standards at 10 ppm, 5 ppm, and 2 ppm. These standards were filtered through a 0.2 μm cellulose acetate filter, transferred to analytical vials, and analyzed. Standard curves for Tinuvin 144 and Tinuvin 292 were then constructed based on the results.
[0296] Next, each solid composition was diluted with THF to prepare a 1% by mass sample solution. These solutions were then filtered through a 0.2 μm cellulose acetate filter, transferred to analytical vials, and analyzed.
[0297] LC-MS determination was performed using an Agilent 1260 series HPLC / 6460MS manufactured by Agilent Technologies. The contents of Tinuvin144 and Tinuvin292 in each solid composition were calculated based on the standard curves of Tinuvin144 and Tinuvin292 and the detection area of each ion (m / z) of each solid composition, and the total amount was set as the content of the piperidine-containing compound.
[0298] <Mass of solid components in the solid composition>
[0299] The mass of solid components in each of the obtained solid compositions was calculated using the following method, and the results were all above 97.0% by mass.
[0300] First, weigh 0.25 g of the solid composition and add it to a metered aluminum cup. Add 4 g of toluene to completely dissolve the solid composition, then heat it at 110°C for 3 hours using a hot air circulating dryer. Next, measure the aluminum cup after the test and determine the mass of the residue. Calculate the mass of the solid component using the following formula.
[0301] Mass of solid components (mass%) = 100 × (mass of residue) / (mass of solid composition)
[0302] [Table 2]
[0303]
[0304] [Manufacturing of Powder Coatings]
[0305] The solid composition is made into powder using a pulverizer.
[0306] Next, powdered mixtures were prepared using powdered solid compositions A-1, A-3, and B-1 to B-5 respectively, following the steps below. For every 100 parts by weight of the powdered solid composition, 67 parts by weight of titanium dioxide (manufactured by DU PONT, Ti-Pure (registered trademark) R960), 25 parts by weight of end-capped isocyanate-based curing agent (manufactured by Evonik, VESTAGON (registered trademark) B1530), 0.4 parts by weight of a xylene solution (100-fold diluted) of dibutyltin dilaurate as a curing catalyst, 0.8 parts by weight of benzoin as a degassing agent, and 2 parts by weight of a surface conditioner (manufactured by BYK-Chemie, BYK (registered trademark)-360P) were added. The mixture was then mixed using a high-speed mixer (manufactured by Yuzaki Co., Ltd.) for approximately 10 to 30 minutes to obtain the powdered mixture.
[0307] In addition, powdered mixtures were prepared using powdered solid compositions A-2 and A-4 respectively, following the steps below. For every 100 parts by weight of the powdered solid composition, 67 parts by weight of titanium dioxide (manufactured by DU PONT, Ti-Pure R960), 27 parts by weight of end-capped isocyanate curing agent (manufactured by Evonik, VESTAGON B1530), 0.4 parts by weight of a xylene solution (100x diluted) of dibutyltin dilaurate as a curing catalyst, 0.8 parts by weight of benzoin as a degassing agent, and 2 parts by weight of a surface conditioner (manufactured by BYK-Chemie, BYK-360P) were added. The mixture was then mixed using a high-speed mixer (manufactured by Yuzaki Co., Ltd.) for approximately 10–30 minutes to obtain the powdered mixture.
[0308] Alternatively, using the powdered solid composition A-5, a powdered mixture was prepared according to the following steps. Relative to 100 parts by weight of the powdered solid composition, 69 parts by weight of titanium dioxide (manufactured by DU PONT, Ti-Pure R960), 68 parts by weight of end-capped isocyanate-based curing agent (manufactured by Sumika Covestro Urethane, Crelan UI), 0.4 parts by weight of a xylene solution (100x diluted) of dibutyltin dilaurate as a curing catalyst, 1.3 parts by weight of benzoin as a degassing agent, and 3 parts by weight of a surface conditioner (manufactured by BYK-Chemie, BYK-360P) were added. The mixture was then mixed using a high-speed mixer (manufactured by Yuzaki Co., Ltd.) for approximately 10 to 30 minutes to obtain a powdered mixture.
[0309] Next, using a twin-screw extruder (THERMO PRISM, 16mm extruder), the powdered mixtures were melt-blended at a barrel setting temperature of 120°C to obtain granules. The resulting granules were then pulverized at room temperature using a pulverizer (FRITSCH, Speed Rotor Mill P14), and classified using a 150-mesh sieve to obtain a powder coating with an average particle size of approximately 40 μm.
[0310] It should be noted that the above-mentioned set temperature (120°C) in the melt mixing process is a temperature lower than the standard boiling point of the solvent contained in the solid composition.
[0311] The contents of ethylbenzene, mixed xylenes, p-xylene, and compounds containing piperidine groups in the powder coating were determined using the same method as those used for the contents of the components in the solid composition.
[0312] In addition, the content of fluorinated copolymers in powder coatings is calculated based on the amount of fluorinated copolymers used in the manufacture of the powder coatings.
[0313] [Manufacturing of substrates with coatings]
[0314] Using the obtained powder coating, an electrostatic coating machine (Onoda Cement Co., Ltd., GX3600C) is used to electrostatically coat one side of an aluminum plate that has undergone chromate treatment, forming a powder coating layer.
[0315] Next, the aluminum plates with each coating layer were kept in an atmosphere of 200°C for 20 minutes.
[0316] After heating, an aluminum plate with a coating layer corresponding to each example is placed and cooled to room temperature to obtain an aluminum plate (coated article) with a coating film (cured film) with a film thickness of 55 to 65 μm.
[0317] [Lightfastness Evaluation]
[0318] The lightfastness of the resulting coating was evaluated using a Q-LAB SE model. Test conditions were performed according to Cycle 3 of ASTM G154-04 (lightfastness test). The lightfastness of the coating was evaluated based on the 60° gloss retention rate of the coating after 8000 hours of testing on this machine, according to the following criteria.
[0319] It should be noted that the 60° gloss retention rate refers to the ratio (in %) of the 60° gloss value of the coating before the lightfastness test (set to 100%) to the 60° gloss value of the coating after the lightfastness test. The gloss retention rate is determined and calculated according to JIS K 5600-4-7:1999 (ISO 2813:1994).
[0320] <Evaluation Criteria>
[0321] 〇 (Excellent): 60° gloss retention rate is over 95%.
[0322] △(Good): 60° gloss retention rate is above 90% and less than 95%.
[0323] × (Unacceptable): 60° gloss retention rate less than 90%
[0324] [Impact resistance]
[0325] The impact resistance of the obtained coating was evaluated using the DuPont method based on JIS K5600-5-3, under conditions of a punch diameter of 1 / 2 inch and a weight of 500g. The drop height (in cm) of the coating without abnormalities was measured, and the impact resistance of the coating was evaluated according to the following criteria.
[0326] <Evaluation Criteria>
[0327] 〇 (Excellent): 35cm and above
[0328] △ (Good): 25cm or more and less than 35cm
[0329] × (Unacceptable): Less than 25cm
[0330] [Table 3]
[0331]
[0332] As shown in Table 3, it can be confirmed that when the solid compositions (solid compositions A-1 to A-5, B-1, B-2) are manufactured and the powder coatings obtained therefrom are used, coatings with excellent lightfastness and impact resistance can be obtained (Examples 1 to 7).
[0333] It should be noted that the entire contents of the specification, claims and abstract of Japanese Patent Application No. 2023-037633, filed on March 10, 2023, are incorporated herein as disclosure of this invention.
Claims
1. A solid composition, characterized in that, It includes: Fluorinated copolymers having trifluorochloroethylene-based units and vinyl ether-based units; Compounds containing piperidine groups; Ethylbenzene; and A mixture of xylenes containing at least two of the following: o-xylene, m-xylene, and p-xylene.
2. The solid composition according to claim 1, wherein, The mixed xylenes contain all of the following: o-xylene, m-xylene, and p-xylene.
3. The solid composition according to claim 2, wherein, The mass ratio of the ethylbenzene content to the mixed xylene content is 0.1 to 7.
0.
4. The solid composition according to claim 2, wherein, The compound containing piperidine is a compound represented by the following formula (N1). In the above formula (1), R 11 ~R 14 Each is independently an alkyl, cycloalkyl, substituted alkyl, aryl, or aralkyl group having 1 to 18 carbon atoms, R 11 and R 12 Or R 13 and R 14 It can be optionally formed into an aliphatic ring with 3 to 6 carbon atoms; R 15 It can be a hydrogen atom, alkyl, substituted alkyl, aryl, aralkyl, or cycloalkyl; R 16 It is a group consisting of a hydrogen atom, a hydroxyl group, an alkyl group, a substituted alkyl group, an aryl group, an aralkyl group, a group containing an ester bond, a group containing an amino group, a group containing a 2,2,6,6-tetrasubstituted piperidinyl group, or a combination of two or more of these groups.
5. The solid composition according to claim 2, wherein, The content of the piperidine-containing compound is 0.01 to 3.0% by mass relative to the total mass of the solid composition.
6. The solid composition according to claim 2, wherein, The mass ratio of the content of the piperidinyl compound to the content of the ethylbenzene is 0.5 to 200.
7. A method for manufacturing a solid composition, characterized in that, A monomer comprising trifluorochloroethylene and vinyl ether is polymerized in the presence of a polymerization solvent, a piperidine-containing compound, and a free radical polymerization initiator to produce a solution comprising a fluorinated copolymer, the polymerization solvent, and the piperidine-containing compound, wherein the polymerization solvent comprises ethylbenzene and a mixture of xylenes containing o-xylene, m-xylene, and p-xylene. At least a portion of the polymerization solvent is removed from the solution to obtain a solid composition comprising the fluorinated copolymer, the piperidine-containing compound, the ethylbenzene, and the mixed xylenes.
8. A powder coating, characterized in that, The solid composition comprises any one of the fluorinated copolymers, piperidine compounds, ethylbenzene, and mixed xylenes containing o-xylene, m-xylene, and p-xylene.
9. A method for manufacturing a coated article, characterized in that, The powder coating of claim 8 is applied to the surface of a substrate to form a coating layer, and the coating layer is cured to form a coating film.
Citation Information
Patent Citations
Information processing system and system management server
JP2023037633A
Fluororesin-containing solution, process for producing fluororesin-containing solution, coating composition, and coated article
WO2017122701A1